Tools for measuring technical skills during gynaecologic surgery: a scoping review - Louise Inkeri Hennings (BMC Medical Education, 2021)
Abstract Background Standardised assessment is key to structured surgical training. Currently, there is no consensus on which surgical assessment tool to use in live gynaecologic surgery. The purpose of this review is to identify assessment tools measuring technical skills in gynaecologic surgery and evaluate the measurement characteristics of each tool. Method We utilized the scoping review methodology and searched PubMed, Medline, Embase and Cochrane. Inclusion criteria were studies that analysed assessment tools in live gynaecologic surgery. Kane’s validity argument was applied to evaluate the assessment tools in the included studies. Results Eight studies out of the 544 identified fulfilled the inclusion criteria. The assessment tools were categorised as global rating scales, global and procedure rating scales combined, procedure-specific rating scales or as a non-procedure-specific error assessment tool. Conclusion This scoping review presents the current different tools for observational assessment of technical skills in intraoperative, gynaecologic surgery. This scoping review can serve as a guide for surgical educators who want to apply a scale or a specific tool in surgical assessment.